Effects of simulated visual acuity and ocular motility impairments on SSVEP brain-computer interface performance: an experiment with Shuffle Speller. Issue 2 (3rd July 2018) - Peters, Betts; Higger, Matt; Quivira, Fernando; Bedrick, Steven; Dudy, Shiran; Eddy, Brandon; Kinsella, Michelle; Memmott, Tab; Wiedrick, Jack; Fried-Oken, Melanie; Erdogmus, Deniz; Oken, Barry
ABSTRACT: Individuals with severe speech and physical impairments may have concomitant visual acuity impairments (VAI) or ocular motility impairments (OMI) impacting visual BCI use. We report on use of the Shuffle Speller typing interface for SSVEP BCI copy-spelling with simulated VAI, simulated OMI, and unimpaired vision. To mitigate the effects of visual impairments, we introduce a method that adaptively selects user-specific trial lengths to maximize expected information transfer rate (ITR), which is shown to closely approximate correct letter selection rate. All participants could type under the unimpaired and simulated VAI conditions, without significant differences in typing accuracy or speed. Most participants (31 of 37) could not type under the simulated OMI condition; some achieved high accuracy with slower typing speeds. Reported workload and discomfort were low, and satisfaction high, under the unimpaired and simulated VAI conditions. Implications and future directions for exploration of visual impairment in BCI use are discussed.